Estimation of Physiological Factors Controlling Carbon Isotope Fractionation in Coccolithophores in Photic Zone and Core‐Top Samples - Iván Hernández‐Almeida; Kristen M. Krumhardt; Hongrui Zhang; Heather M. Stoll (Geochemistry, Geophysics, Geosystems, 2020)
Abstract Estimates of past pCO2 prior to ice‐core records have often been sought by measuring carbon isotopic fractionation during photosynthesis (Ɛp) in alkenone‐producing algae present in the fossil record. Photic zone and core‐top Ɛp show strong latitudinal gradients, which have been interpreted as an effect of growth rate. The factor b, used in previous studies to account for the changes in growth rate, shows high dependence on [CO2]aq in culture experiments, making difficult the deconvolution of nutrients versus other effects in the field. We combine coccolithophore growth rate output from a global model, limited by sea surface temperature (SST) and [PO43−] with a statistical model that include [CO2]aq, cell size and light to predict Ɛp, and examine the influence of different environmental and physiological variables on the observed expression of Ɛp in field samples. Back calculations of the growth rate necessary to match the observed Ɛp in photic zone and core‐top samples using the statistical model show high correlation with modeled growth rates using [PO43−] and SST in temperate regions. For Southern Ocean and tropical upwelling regions, with colder and warmer SST, respectively, there might be additional factors controlling growth rate not accounted for in the model, such as grazing or nutrient recycling. We evaluate the potential to reconstruct past growth rates using planktonic foraminifera‐ and coccolithophore‐based proxies related to water column structure. We found best application of these proxies as potential indicators of past [PO43−], which can subsequently be used in combination with proxy temperature, to estimate past coccolithophore growth rates.